(untitled) (Nordic Journal of African Studies, 1999)
The majority of African nations have not been able or willing to realign their policy frameworks to combat the deepening crisis of development that has plagued them during the past two decades. In particular, sub-Saharan Africa, with its undiversified economic structure and undeveloped policy infrastructure, has been immobilized by its inability to adjust to the external and internal shocks it has experienced. This paper discusses and analyses recent policy reform initiatives by the Global Coalition for Africa for addressing Africa’s tragic decline and marginalization.